1994
DOI: 10.1207/s15327752jpa6202_10
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profiles Distinguishing Litigating and Nonlitigating Pain Patients: Subtle, and Not So Subtle

Abstract: Chronic pain patients in the midst of litigation over settlement for their injuries were examined as a naturally occurring group where one might expect various distortions or differences in test findings on the Minnesota Multiphasic Personality Inventory-Revised (MMPI-2). Similar groups of 43 chronic pain patients in litigation and 45 not in litigation were examined on 10 key MMPI-2 variables selected a priori. Multivariate analysis of variance revealed a significant difference between groups (p = .036). Litig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Financial compensation issues in the context of mild traumatic brain injury (MTBI) have been a source of controversy for many years (Binder, Trimble, & McNiel, 1991;Cook, 1972;Dush, Simons, Platt, Nation, & Ayres, 1994;Mendelson, 1995;Miller, 1961). In a review of effects of MTBI, Binder and Rohling (1996) reported a moderate effect size (ES 0.47) for ®nancial compensation seeking across numerous studies assessing a variety of dependent variables.…”
Section: A Longitudinal Study Of the Relationship Between Financial Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial compensation issues in the context of mild traumatic brain injury (MTBI) have been a source of controversy for many years (Binder, Trimble, & McNiel, 1991;Cook, 1972;Dush, Simons, Platt, Nation, & Ayres, 1994;Mendelson, 1995;Miller, 1961). In a review of effects of MTBI, Binder and Rohling (1996) reported a moderate effect size (ES 0.47) for ®nancial compensation seeking across numerous studies assessing a variety of dependent variables.…”
Section: A Longitudinal Study Of the Relationship Between Financial Cmentioning
confidence: 99%
“…First, were there demographic or injury-related variables that predicted the people likely to be seeking or receiving ®nancial compensation? Given previous research (Dush et al, 1994;Youngjohn et al, 1997), we predicted that no demographic variables currently assessed (i.e., gender, age, injury severity, socioeconomic status [SES], years of education) would predict the choice to pursue compensation after MTBI. Second, was level of self-reported symptom incidence associated with pursuit of compensation?…”
Section: A Longitudinal Study Of the Relationship Between Financial Cmentioning
confidence: 99%
“…Claimants may also be counselled by attorneys and support groups who further stimulate their fears. We have also found, in samples of patients with chronic pain, that those in litigation tend to ( a ) report more symptoms, particularly obvious rather than subtle clinical symptoms used for differential diagnosis, or ( b ) favour physical rather than psychological explanations for symptoms 29. These may be selectively symptoms that are more easily reattributed to injury related concerns.…”
Section: Mass Somatisationmentioning
confidence: 64%
“…It was suggested that a likely explanation for this was that this technique is essentially a measure of psychiatric difficulties and would not be appropriate for the identification of malingering in pain. On review of the literature, it was noted that some MMPI/MMPI-2 studies involving a differential prevalence design had found that those who are litigating or involved in a compensation claim have higher clinical and/or validity scale elevations (e.g., Dush et al, 1994;Harness & Chase, 1994), whereas others have not found such differences (e.g., Melzack et al, 1985;Trabin, Rader, & Cummings, 1987). suggested that compensation patients are clinically similar to noncompensation patients in the relative frequency of cases of psychological disturbance or in which there has been potentiation of psychophysiological reactivity.…”
Section: Questionnairesmentioning
confidence: 99%